PENERAPAN MODEL KOOPERATIF TIPENUMBER HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 19 BATANG DUKU - Joko Santoso; Lazim N Lazim N; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the low of IPA achievement in fourth grade students of SD Negeri 19 Batang Duku, with an average grade 58.50. While the value of a minimum completeness criteria (KKM) IPA is 65. Among the ten students, only three students who reach KKM. This research is a Classroom Action Research (CAR) conducted aims to increase IPA achievement of Elementary School fourth grade students 19 Batang Duku by applying the cooperative learning type Number Heads Together. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results of studying the data obtained from the average results of study before action 58.50 to 17.94% to 69.00 in cycle I. In the second cycle increased to 11.59% with an average of 77.00. The activities of teachers in the first cycle of the first meeting to obtain a percentage of 67.85% with the good category, at the second meeting has increased with the percentage of 71.42% both categories. Furthermore, the first meeting of the second cycle of teacher activity also increased with the percentage of 85.71% is very good category and at the second meeting of the second cycle increased again with a percentage of 96.42% is very good category. Activity of students in the first cycle of the first meeting to obtain the percentage of 67.85% less category, at the second meeting has increased by 75% the percentage of both categories, the students begin to understand this cycle of learning activities by applying the type Number Heads Together (NHT) is characterized by the activity of students in the first meeting of the second cycle increased with the percentage of 85.71% is very good category. At the second meeting of the second cycle increased with the percentage of 92.85% is very good category. This research in the fourth grade Elementary School 19 Batang Duku prove that the application of the Number Heads Together (NHT) can increase IPA achievement of fourth grade students of SD Negeri 19 Batang Duku.Keywords : Model Number Heads Together (NHT), IPA achievement